Pain sensitivity differs between dog breeds but not in the way veterinarians believe - Caddiell, Rachel M. P.; Cunningham, Rachael M.; White, Philip A.; Lascelles, B. Duncan X.; Gruen, Margaret E. (Frontiers in Pain Research, 2023)
Background: Veterinarians hold distinct breed-specific pain sensitivity beliefs that differ from the general public but are highly consistent with one another. This is remarkable as there is no current scientific evidence for biological differences in pain sensitivity across dog breeds. Therefore, the present study evaluated whether pain sensitivity thresholds differ across a set of dog breeds and if so, whether veterinarians' pain sensitivity ratings explain these differences or if these ratings are attributed to behavioral characteristics. Methods: Pain sensitivity thresholds (using quantitative sensory testing (QST) methods) and canine behavior (using owner questionnaires and emotional reactivity tests) were prospectively measured across selected dog breeds. Adult, healthy dogs from ten dog breeds / breed types were recruited, representing breeds subjectively rated by veterinarians as This is a provisional file, not the final typeset article high (chihuahua, German shepherd, Maltese, Siberian husky), average (border collie, Boston terrier, Jack Russell terrier), or low (golden retriever, pitbull, Labrador retriever) pain sensitivity. A final sample of 149 dogs were included in statistical analyses. Results: Veterinarians' pain sensitivity ratings provided minimal explanation for pain sensitivity thresholds measured using QST in dogs; however, dog breeds did differ in their pain sensitivity thresholds across QST methods evaluated. Breed differences were observed for some aspects of emotional reactivity tests; however, these behavioral differences did not explain the differences in pain sensitivity thresholds found. Veterinarians' pain sensitivity ratings were positively associated with dog approach scores for the disgruntled stranger test suggesting the way dogs greet strangers, may be a factor influencing veterinarians' ratings of pain sensitivity across dog breeds. Conclusions and clinical relevance: Overall, these findings highlight a need to investigate biological mechanisms that may explain breed differences in pain sensitivity as this may inform pain management recommendations. Further, future research should focus on when and how these breed-specific pain sensitivity beliefs developed in veterinarians, as veterinarians' beliefs could impact the recognition and treatment of pain for canine patients.